The social location of harm from others' drinking in 10 societies. (5th November 2018) - Room, Robin; Callinan, Sarah; Greenfield, Thomas K.; Rekve, Dag; Waleewong, Orratai; Stanesby, Oliver; Thamarangsi, Thaksaphon; Benegal, Vivek; Casswell, Sally; Florenzano, Ramon; Hanh, Hoang T.M.; Hettige, Siri; et al.
Abstract: Aims: Survey data from 10 diverse countries were used to analyse the social location of harms from others' drinking: which segments of the population are more likely to be adversely affected by such harm, and how does this differ between societies? Methods: General‐population surveys in Australia, Chile, India, Laos, New Zealand, Nigeria, Sri Lanka, Thailand, United States and Vietnam, with a primary focus on the social location of the harmed person by gender, age groups, rural/urban residence and drinking status. Harms from known drinkers were analysed separately from harms from strangers. Results: In all sites, risky or moderate drinkers were more likely than abstainers to report harm from the drinking of known drinkers, with risky drinkers the most likely to report harm. This was also generally true for harm from strangers' drinking, although the patterns were more mixed in Vietnam and Thailand. Harm from strangers' drinking was more often reported by males, while gender disparity in harm from known drinkers varied between sites. Younger adults were more likely to experience harm both from known drinkers and from strangers in some, but not all, societies. Only a few sites showed significant urban/rural differences, with disparities varying in direction. In multivariate analyses, most relationships remained, although some were no longer significant. Conclusion: The social location of harms from others' drinking, whether known or a stranger, varies considerably between societies. One near‐commonality among the societies is that those who are themselves risky drinkers are more likely to suffer harm from others' drinking.